2014
DOI: 10.1186/1751-0759-8-8
|View full text |Cite
|
Sign up to set email alerts
|

Rational/antiemotional behaviors in interpersonal relationships and the functional prognosis of patients with rheumatoid arthritis: a Japanese multicenter, longitudinal study

Abstract: BackgroundThe repression of negative emotions is a personality factor that received considerable attention in the 1950-60s as being relevant to the onset and course of rheumatoid arthritis (RA). Despite subsequent, repeated criticisms of the cross-sectional nature of the earlier studies, even to date few prospective studies have been reported on this issue. This multicenter study prospectively examined if “rational and antiemotional” behavior (antiemotionality), characterized by an extreme tendency to suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Nagano and al. (17) showed that, for RA patients, rational/anti-emotional behaviors, characterized by an extreme tendency to squelch emotional behaviors and rationalize negative experiences, was associated with poorer prognoses. Ishii and al.…”
Section: Discussionmentioning
confidence: 99%
“…Nagano and al. (17) showed that, for RA patients, rational/anti-emotional behaviors, characterized by an extreme tendency to squelch emotional behaviors and rationalize negative experiences, was associated with poorer prognoses. Ishii and al.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective examination of 532 patients in Japan with rheumatoid arthritis found that "rational and anti-emotional behaviour," measured using patients' responses to a questionnaire, was linked with poorer functional outcome two years later. 22 Another Japanese study found that mood disturbances after mastectomy were greater in women who scored more highly in assessments of emotional suppression before surgery. 23 This recalls Carl Rogers's idea that expressing emotion, far from reflecting more serious mental health concerns, may help to alleviate them.…”
Section: Longer Survivalmentioning
confidence: 99%